Decolonial love : salvation in colonial modernity - Drexler-Dreis, Joseph (Fordham University Press, 2019)
Bringing together theologies of liberation and decolonial thought, Decolonial Love interrogates colonial frameworks that shape Christian thought and legitimize structures of oppression and violence within Western modernity. In response to the historical situation of colonial modernity, the book offers a decolonial mode of theological reflection and names a historical instance of salvation that stands in conflict with Western modernity. Seeking a new starting point for theological reflection and praxis, Joseph Drexler-Dreis turns to the work of Frantz Fanon and James Baldwin. Rejecting a politics of inclusion into the modern world-system, Fanon and Baldwin engage reality from commitments that Drexler-Dreis describes as orientations of decolonial love. These orientations expose the idolatry of Western modernity, situate the human person in relation to a reality that exceeds modern/colonial significations, and catalyze and authenticate historical movement in conflict with the modern world-system. The orientations of decolonial love in the work of Fanon and Baldwin--whose work is often perceived as violent from the perspective of Western modernity--inform theological commitments and reflection, and particularly the theological image of salvation. Decolonial Love offers to theologians a foothold within the modern/colonial context from which to commit to the sacred and, from a historical encounter with the divine mystery, face up to and take responsibility for the legacies of colonial domination and violence within a struggle to transform reality.